Evaluation of real time rain-rate on downlink satellite signal attenuation in Abuja, Nigeria - Tijani, Alhassan; Yusuf, Samson D.; Ibrahim, Umar; Loko, Abdulmumini Z.; Mundi, Abdullahi A. (EDUCATUM Journal of Science, Mathematics and Technology, 2020)
Natural phenomenon and other human activities in the atmosphere have caused serious variations in rainfall which leads to rain-rates that has resulted in the mitigation of signal transmission in satellite communication. This is due to absorption and scattering of the radio waves, resulting in the reduction of the overall link availability. In this study, the cumulative distribution functions (CDFs) for the predicted rain rate and rain attenuation in Abuja, Nigeria was evaluated using the Moupfouma and Chebil models purposely designed for tropical regions. One year data of signal attenuation and amount of rainfall in the study area for 2018 was collected from Nigerian Communication Satellite limited (NIGECOMSAT) and Nigeria Metrological Center (NiMET). The Ajayi (ITU-R P) models alongside with relevant statistics were employed for evaluation of the rain attenuation in the study area. Results show that the highest rainfall value with mean of 128.07 mm was recorded in August while the lowest value 01.87 m was recorded in November. The  estimated value of rain-rate in the study area were 1.95 mm/hr and 5.57 mm/hr in August and September with high attenuation value of 11.01dB – 19.67dB and 15.84dB – 18.64dB both on C – band and Ku – band. The result Show that, attenuation due to rain in the frequency above 10GHz is much higher than that for frequency of 4GHz. Therefore, as the size of the rain drop approaches the wavelength of the signal, the more it absorbs its strength and the higher the rain rate attenuation on signal. The result is useful for designing highly reliable microwave links in the study area.